Theotônio dos Santos (1936-2018) y la reconstrucción de la economía política del desarrollo - DOMÍNGUEZ-MARTÍN, Rafael (Revista Iberoamericana de Estudios de Desarrollo)
This essay analyzes economic thought trajectory of the great Latin American intellectual Theotônio dos Santos in his vital context and the history of ideas, as well as his main contributions to the critical studies of development.